2022
DOI: 10.1002/joc.7521
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal climatology of correlations between the planetary boundary layer height and surface meteorological factors over the contiguous United States

Abstract: The correlations between the planetary boundary layer height (PBLH) and surface meteorological factors, including the surface wind speed (RWS), temperature (RTS), specific humidity (RSH), pressure (RPS), and lower tropospheric stability (RLTS), are investigated using hourly profiles from the Aircraft Meteorological Data Reports at 54 major airports over the contiguous United States (CONUS) and surface observations from weather stations. At the diurnal cycle, the RWS and RTS are positive and the RPS and RLTS ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…Consistent with the results of the model validation in this paper, WS plays a major dominant role in the development of SBLH. This paper also found a strong positive correlation between SBLH and WS and LST, which is consistent with the findings in the interior of the United States [61], because the SBL stability is gradually enhanced during the night-time by the influence of the increased temperature difference between the surface and the atmosphere, and the WS is able to influence the degree of air mixing in the SBL. Unlike Wuhan [7], which is in the monsoon zone, this paper found a weak negative correlation between SBLH and RH, while Wuhan has a weak positive correlation, which may be affected by the regional dominant wind direction and latitude difference.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with the results of the model validation in this paper, WS plays a major dominant role in the development of SBLH. This paper also found a strong positive correlation between SBLH and WS and LST, which is consistent with the findings in the interior of the United States [61], because the SBL stability is gradually enhanced during the night-time by the influence of the increased temperature difference between the surface and the atmosphere, and the WS is able to influence the degree of air mixing in the SBL. Unlike Wuhan [7], which is in the monsoon zone, this paper found a weak negative correlation between SBLH and RH, while Wuhan has a weak positive correlation, which may be affected by the regional dominant wind direction and latitude difference.…”
Section: Discussionsupporting
confidence: 90%
“…Despite the relatively weak impact of TCC , the influence of other meteorological variables such as the PS , T 2m , Q 2m , T , and Q was significant, with importance values of 9.3%, 6%, 5.9%, 5.3%, and 4.8%, respectively. High‐pressure conditions tend to suppress PBL development due to subsidence, explaining the weak negative correlation between the surface pressure and the PBLH MOSAiC ( R = −0.36) (J. Guo et al., 2016; Seidel et al., 2012; Xi et al., 2022) (Figure 6). Furthermore, it's worth noting that a bias in the T 2m can lead to buoyancy effects.…”
Section: Resultsmentioning
confidence: 99%
“…Step Data acquisition and matching. Consistent with previous research on the development of boundary layers (J. Guo et al., 2016, 2021, Seidel et al., 2010, 2012; Xi et al., 2022; W. Zhang et al., 2016, 2018; Y. Zhang et al., 2020), multiple factors were considered for the prediction of PBLH using the RF model, including near‐surface meteorological factors, atmospheric parameter profiles, and cloud cover. Specifically, the PBLH ERA5 , WS, T, Q, PS, T 2m , Q 2m , U 10m , V 10m , and TCC were selected as the input variables, and the PBLH MOSAiC was selected as the predicted variable.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…The observed and simulated PBLHs obtained by the abovementioned definition are compared (Figure 11). The higher daytime PBLHs on the strong-UHI days than on the Frontiers in Earth Science frontiersin.org weak-UHI days may be 1) due to the higher sensible heat flux (Figure 9, 11), which is demonstrated by Dang et al (2016), who found a strong positive correlation between surface sensible heat fluxes and PBLH, and 2) higher surface temperature that is found to be positively correlated with PBLH (Xi et al, 2022; Figure 5A). The models underestimate…”
Section: Model Performances For Pbl Heightmentioning
confidence: 93%